Triggering of viral and bacterial respiratory infection hospitalizations by traffic pollution exposure in a cohort of hospitalized adults - Daniel P. Croft; Md Rayhanul Islam; Kelly Thevenet-Morrison; Carl J. Johnston; Mark J. Utell; Philip K. Hopke; Steve N. Georas; Augusto A. Litonjua; Derick R. Peterson; Soumyaroop Bhattacharya; Andrea Baran; Chinyi Chu; et al. (PLoS ONE, 2026)
The rate of respiratory viral infection (RVI) associated with acute air pollution exposure is well established, but whether bacterial and viral infections respond similarly to traffic related air pollution (TRAP) exposure is less well understood. Using a novel seasonal time-stratified case-crossover design and conditional logistic regression, we separately estimated the rate of hospitalization for 465 patients with RVI, respiratory bacterial infection (RBI), or combined respiratory viral and bacterial infection (RVBI) associated with increased ambient particulate matter ≤2.5 µm (PM 2.5 ), black carbon (BC), nitrogen dioxide (NO 2 ) and carbon monoxide (CO) concentrations in the previous 1, 2, and 3 weeks (lag days 0–6, 7–13, 14–20). In a novel approach, a four-physician panel adjudicated each case of infection to accurately classify the type of infection present and only patients with the highest diagnostic certainty were enrolled in this study. Associations were strongest between TRAP and RVI at the 0–6 lag period, with fewer, less precise associations at later lag times for RVBI and RBI. Each 2.6 µg/m 3 increase in PM 2.5 on lag days 0–6 was associated with a 22.1% increased rate of RVI hospitalization (95% CI: 1.6%, 46.7%). Each 0.1 µg/m 3 increase in BC was associated with a 30.0% increase (95% CI: 5.0%, 61.1%) in the rate of hospitalization for RVI. Rates of hospitalization for RVI associated with increased PM 2.5 were generally largest for lag days 0–6 and 7–13. The RVI/BC rate ratio was larger for females than males for days 0–13, but not for PM 2.5 and NO 2 . Short term increases in PM 2.5 , BC, NO 2 , and CO concentrations (markers of traffic pollution) were associated with an increased rate of RVI hospitalization, while sex-specific associations were observed between BC and RVI for females. Further study of the mechanism underlying the effect of TRAP on RVI is needed.